MICROSPECTROPHOTOMETRY AND THE PHOTORECEPTOR OF PHYCOMYCES I - Wolken, Jerome J. (The Rockefeller University Press, 1969)
By applying microspectrophotometry to the sporangiophore of Phycomyces blakesleeanus wild-type and the albino car-10(-) type II, absorption spectra were obtained for 1- to 5-day cultures. Spectra in the growing-zone of the wild-type during Stage IVb, taken from 0.1 to 3 mm below the base of the sporangium, show two distinctly different spectra: one is more characteristic of a carotene, the other of a flavin. Combined, these absorption spectra reproduce closely the action spectrum. For the albino car-10(-), which is deficient in carotenes, only the spectrum characteristic of lumichrome or a reduced flavin was found. A c-type cytochrome was isolated from both strains which, if coupled with a flavin, could permit a photoreversible oxidation-reduction system. Birefringent crystals were observed to be aligned in the growing zone in which the photoreceptor is believed to lie. Micro-spectrophotometry of these crystals shows absorption peaks similar to those of riboflavin crystals.